Source and Myth : Opera in Italian Cinema of the 1960s - Giuggioli, Matteo (Journal of Film Music, 2019)
Going back to the early days of film, Italian cinema's attraction to opera showed no sign of abating in the aftermath of World War II, albeit with a change of direction and and an expansion into new expressive and semantic paths. The initiator of the new direction was Luchino Visconti in the 1950s, followed by a new generation of renowned Italian film directors in the 1960s. in the heated social, political, and artistic environment of the "economic miracle," Italian cinema of the 1960s first and foremost questioned the symbolic status that opera had acquired and maintained in Italian popular culture throughout the first half of the century. Prominent film directors identified opera as a relevant object for their critical inquiries into the controversial nation-building process and the customs of the Italian people. This article focuses on three films in which excerpts from opera activate complex intertextual plots: Valerio Zurlini's Girl with a Suitcase (1961), Bernardo Bertolucci's Before the Revolution (1964), and Marco Bellocchio's China is Near (1967). Against a backdrop of such different cinematic experiences, the article shows how opera acquired the common profile and value of a sublime and troubled mythology in 1960s Italian film culture.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTU1OC9qZm0uMzczMTg